The Value of Antibiotics, Aureomycin B12 supplement (Aurofac 2A) and Vitamin B2 Premix (Fortafeed 2-49-C) in the protein supplement for fattening spring pigs in the dry lot in summer. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
In 1955-56 experiments were designed with swine to secure information on the maximum use of alfalfa meal in protein supplemental mixtures as a substitute for pasture in the dry lot, since pastures for swine in Kansas are often poor, inadequate or unavailable. The pigs in these tests received, with their grain mixed protein supplements which contained varying quantities of alfalfa meal. The mixed protein supplement that gave best results for the two years tested was one of 4 parts tankage, 4 parts soybean meal, and 3 parts alfalfa meal.
Keywords: Swine; Aureomycin B12; Vitamin B2; Protein